One in 5 athletes sustain reinjury upon return to high-risk sports after ACL reconstruction: A systematic review in 1239 athletes younger than 20 years - Barber-Westin, S.; Noyes, F. R. (Sports Health: A Multidisciplinary Approach, 2020)
Context: Anterior cruciate ligament (ACL) reconstruction (ACLR) is frequently performed in patients younger than 20 years whose goal is to return to sport (RTS). Varying reinjury rates have been reported, and the factors responsible are unclear. Studies differ with regard to age, graft type, surgical techniques, postoperative rehabilitation, RTS guidelines, and methods used to determine ACL failures.